A Handover Planning Optimization Technique For 5G Systems - Indra, Win Adiyansyah; Saptari, Adi; Che Aziz, Siti Asma; Irianto; M.A., Wong; Syed Salim, Syed Najib (Medwell Publications, 2020)
This study investigated the handover planning optimization technique for 5th generation system at selected location, Bukit Beruang, Malacca, Malaysia, based on its varies altitudes and high populated area. By utilizing wireless network design platform, Atoll, added with Global Mapper 15 and Earth Explorer, 99.25% of the total selected zone are in soft handover zone with majority, 63.8% are in softer handover zone. The rest 0.75% are in blank spot zone, no handover due to no signal this is because extreme, varied altitude of terrain, land contour and condition of the area. Repeater and satellite can solve this no signal small zone.